Dampak Kenaikan Tarif Dasar Listrik Terhadap Kinerja Sektor Pertanian di Indonesia dalam Jangka Pendek dan Panjang - Sahara, Sahara (Universitas Sebelas Maret, 2007)
Increasing on electricity price by Indonesian Government in 2001 by 17.47% and 2002 by 24% not only has negative impact on industry sectors but also on agricultural sectors. This paper aims to analysis impact on agricultural sectors performance with using a Recursive Dynamic Computable General Equilibrium (CGE) Model, namely “INDOF model”. The simulation indicates both in the short run and long run increasing on electricity price will reduce industry output, household consumption and employment in agricultural sectors. Besides that the policy will increase price of agricultural product. The negative impacts except household consumption are higher in the long run than that in the short run.